Instrument Refinement for Measuring Self-Efficacy for Competence in Interprofessional Collaborative Practice: Development and Psychometric Analysis of IPECC-SET 27 and IPECC-SET 9. Issue 1 (2nd January 2019) - Kottorp, Anders; Keehn, Mary; Hasnain, Memoona; Gruss, Valerie; Peterson, Elizabeth
ABSTRACT: Assessing competence in interprofessional collaborative practice (ICP) among health professions students is a high priority. This cross-sectional study built on the authors' prior work that led to the development of the 38-item Interprofessional Education Collaborative Competency Self Efficacy Tool (IPECC-SET), an instrument to evaluate health professions students' self-efficacy in interprofessional collaborative competency, and addressed two primary questions. First, could a unidimensional scale based on the IPEC competencies and assessing perceived self-efficacy for competence in ICP and be constructed? Second, could a shorter version of that instrument still meet criteria for unidimensionality and retain the ability to separate students in distinct levels of perceived self-efficacy for competence in ICP? Study participants were two cohorts of students from 11 health professions programs participating in an institutional interprofessional immersion event in 2015 and 2016. Statistical stepwise analyses were conducted using a Rasch rating scale model. The original 38 IPECC-SET items did not meet the criteria to generate a valid unidimensional measure of self-efficacy for competence in ICP, but could be condensed into a 27-item scale that met all set criteria for unidimensionality, with an explained variance of 61.2% and a separation index of 3.02. A shorter, 9-item scale demonstrated a separation index of 2.21. The nine items included also demonstrated a relatively equivalent range (54.93–45.65) as compared to the 27-item scale (57.26–46.16). Findings confirm empirically the conceptual suggestion from our earlier work that the four dimensions in the original IPEC competencies contribute to a shared underlying construct: perceived competence in interprofessional collaboration. Given the emphasis on ICP, psychometrically sound instruments are needed to evaluate the effectiveness of educational efforts to promote competency for ICP. Based on the findings from this study, both the IPECC-SET 27 and IPECC-SET 9 can be used to measure perceived self-efficacy for competence in ICP.